1984
DOI: 10.1007/bf02555636
|View full text |Cite
|
Sign up to set email alerts
|

Increase of mitotic activity in the colonic mucosa of patients with colorectal cancer

Abstract: A histologic and histochemical study of the colonic mucosa, including a study of the mitotic index, was performed in routinely processed specimens from control and tumor-bearing patients. A significant increase in the mitotic index (number of mitosis X 1000 gland cells), without concomitant modifications in the distribution of mitotic figures along the crypt depth, in mucosal thickness, or in mucin secretion, was demonstrated in the colonic mucosa of patients with colonic or rectal cancer compared with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In the current study, lncTCF7 silencing inhibited SW-620 and HT29 cell cycle transition from G1 to S phase, which indicated that lncTCF7 silencing may inhibit SW-620 and HT29 proliferation by suppressing cell cycle progression. Proliferation and cell cycle dysfunction serve an important role in CRC development, and cell migration and invasion serve a central role in CRC metastasis (22)(23)(24). The results of the present study also indicated that lncTCF7 silencing inhibited CRC development and metastasis, indicating that lncTCF7 may function as an oncogene to promote CRC development and metastasis.…”
Section: Discussionsupporting
confidence: 68%
“…In the current study, lncTCF7 silencing inhibited SW-620 and HT29 cell cycle transition from G1 to S phase, which indicated that lncTCF7 silencing may inhibit SW-620 and HT29 proliferation by suppressing cell cycle progression. Proliferation and cell cycle dysfunction serve an important role in CRC development, and cell migration and invasion serve a central role in CRC metastasis (22)(23)(24). The results of the present study also indicated that lncTCF7 silencing inhibited CRC development and metastasis, indicating that lncTCF7 may function as an oncogene to promote CRC development and metastasis.…”
Section: Discussionsupporting
confidence: 68%
“…The MI does not correspond exactly to the labeling index with 3H-thymidine, the latter reaching higher values than the former in the human ileum and colon. 18,20,21 In fact, cells may be labeled by 3H-thymidine, which do not divide further but are shed in the G2-phase of the cell cycle.20 Moreover, the MI depends on the relative number of mucosal cells undergoing mitosis at a given time, whereas the labeling index collects information over an interval of time. Caution must therefore be used when comparing data obtained by the two methods.…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% of colorectal cancer occurs sporadically, having its origins in a multi‐step process of carcinogenesis involving an accumulation of multiple somatic mutations in the colonic epithelium 2 . Expansion of the proliferative zone within the colonic epithelium, secondary to luminal factors, increases the possibility of occurrence of the sequential mutations that lead to cancer 3 . The intestinal lumen is host to a very large number of bacteria and these bacteria or their metabolites are prime candidates for the etiological agents of cancer.…”
Section: Introductionmentioning
confidence: 99%